Performance evaluation of gasoline alternatives using a thermodynamic spark-ignition engine model. Issue 9 (25th September 2017) - Gschwend, Dominik; Soltic, Patrik; Edinger, Philip; Wokaun, Alexander; Vogel, Frédéric
Abstract : In light of climate change and the fact that surface transportation heavily relies on internal combustion engines, many different alternatives to gasoline have been proposed. Abstract : In light of climate change and due to the fact that surface transportation heavily relies on internal combustion engines, many different alternatives to gasoline have been proposed. Herein, we present a model, incorporating only first order effects, which allows a quick assessment of the suitability of a certain molecule as a replacement for gasoline. Using global sensitivity analysis, the elemental composition and the vapor heat capacity have been identified as main influencing fuel parameters. A case study using the currently proposed alternative fuels (methanol, ethanol, n -butanol, dimethylfuran, methylfuran, and α-pinene) as well as gasoline and several hydrocarbons (cyclohexane, n -heptane, isooctane, and benzene) revealed n -butanol as the best performing alternative fuel. The use of this compound entails a significant decrease in CO2 emissions and an increased efficiency, but also a higher consumption in comparison with gasoline.